Nutritional evaluation and growth of infants in a Rwandan neonatal follow‐up clinic. Issue 4 (11th June 2020) - Bradford, Jessica; Beck, Kathryn; Nshimyiryo, Alphonse; Wilson, Kim; Mutaganzwa, Christine; Havugarurema, Silas; Ngamije, Patient; Uwamahoro, Alphonsine; Kirk, Catherine M.
Abstract: Children born preterm, low birth weight (LBW) or with other perinatal risk factors are at high‐risk of malnutrition. Regular growth monitoring and early intervention are essential to promote optimal feeding and growth; however, monitoring growth in preterm infants can be complex. This study evaluated growth monitoring of infants under 6 months enrolled in Paediatric Development Clinics (PDCs) in rural Rwanda. We reviewed electronic medical records (EMR) of infants enrolled in PDCs before age 2 months with their first visit between January 2015 and December 2016 and followed them until age 6 months. Nurse classification of anthropometric measures and nutritional status were extracted from the EMR. Interval growth and length‐for‐age, weight‐for‐length, and weight‐for‐age z‐scores were calculated using World Health Organization anthropometry software as a 'gold standard' comparison to nurse classifications. Two hundred and ninety‐four patients enrolled and had 2, 033 visits during the study period. Referral reasons included prematurity/LBW (73.8%) and hypoxic ischemic encephalopathy (28.2%). Nurses assessed interval growth at 58.7% of visits, length‐for‐age at 66.4%, weight‐for‐length at 65.6% and weight‐for‐age at 66.4%. Nurses and gold standard assessment agreed on interval growth at 53.3% of visits and length‐for‐age at 63.7%, weight‐for‐length at 78.2% and weight‐for‐age at 66.3%. At 6 months, 46.5% were stunted, 19.9% were wasted and 44.2% were underweight. There were significant challenges to optimizing growth and growth monitoring among high‐risk infants served by PDCs, including incomplete and inaccurate assessments. Developing tools for clinician decision support in assessing growth and providing specialized nutritional counselling are essential to supporting optimal outcomes in this population.